Unveiling the Analysis of Gd3+ Doping on Structural, Compositional and Morphological Studies of Zn0.5Mg0.5GdxFe(2-x)O4 Ferrites - Ram, Ghewar; Singh, Ummed; Ram, Sahi; Himanshu; Suthar, Deepak (Asian Journal of Chemistry, 2025)
This study reports the structural, morphological and compositional properties of a series of gadolinium doped Zn0.5Mg0.5GdxFe(2-x)O4 ferrites where x = 0.0, 0.04, 0.08 and 0.12. The ferrites were synthesized using a co-precipitation method and their properties were analyzed using X-ray diffraction (XRD), scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FT-IR). The XRD results showed that the ferrites had both cubic and tetragonal spinal structures. The lattice constants and crystallite sizes of the ferrites were found to vary with the Gd3+ substitution level. The SEM images revealed that the ferrites consisted of nanoparticles of varying sizes and shapes, exhibiting a certain level of agglomeration. The FT-IR spectra confirmed the presence of characteristic M–O vibrations, indicating the successful formation of ferrite structures. These results suggest that the structural and morphological properties of Gd-doped Zn0.5Mg0.5GdxFe(2-x)O4 can be tailored by adjusting the Gd3+ substitution level.